Methane production from natural gas hydrates: reactor details and experimental activities - CASTELLANI, BEATRICE; FILIPPONI, MIRKO; PRESCIUTTI, ANDREA; GAMBELLI, ALBERTO MARIA; MINELLI, Giorgio; BARCHI, Massimiliano Rinaldo; NICOLINI, ANDREA; ROSSI, Federico; COTANA, Franco (Morlacchi Editore, Perugia, 2017)
Natural gas hydrates (NGH) are solid structures in which methane is trapped inside cages constituted of water molecules. They are present in marine and permafrost environments and are considered a much more abundant source of natural gas than conventional deposits. Several methods have been proposed for recovering gaseous methane (thermal stimulation, depressurization for instance). One promising and innovative technique to address the current energy needs and mitigate climate changes is the replacement of methane with carbon dioxide inside the hydrates’ cages. To reproduce marine sediments and permafrost regions, a lab-scale reactor has been designed, manufactured and assembled. Tests show that the reactor is suitable for methane hydrate formation. The experimental future campaigns have several objectives. Firstly, the investigation aims at simulating the CO2-CH4 exchange process and the methane recovery through the use of mechanical devices such as membranes. In addition, geological and mechanical properties of the reproduced hydrates will be evaluated. Finally, experimental results will be used for environmental impact analysis in order to prove the sustainability of the process.